(untitled) (Eurasian Medical Research Periodical, 2023)
Mild to moderate traumatic brain injury (CBI) dominates the overall neurotrauma structure (80-90%). Despite a relatively good prognosis for mental recovery, in these cases, about 10-15% (according to some data, up to 30%) of patients with mild and about 50% of patients with moderate degrees of CHT develop chronic (persisting for several years after the injury) cognitive deficits.